Analysis and Prediction of Minimum Temperatures in Kurdistan Province Using Climatic Scenarios - Ali Mohammad Khorshiddoust; saeed jahanbakhshasl; zahra abbasighasrik; fatemeh abbasighasrik (نشریه جغرافیا و برنامه‌ریزی, 2023)
Today, long-term forecasting of climate variables has received much attention in order to be aware of the extent of change and, consequently, to take the necessary measures to mitigate the adverse effects of climate change. In this study, minimum temperatures in Kurdistan province were predicted using LARS-WG6 downscaling for the next three 20-year periods (2040-2021, 2060-2041, 2080-2061). For this purpose, the HadGEM2-ES general circulation model and three scenarios of RCP8.5, RCP4.5 and RCP2.6 were used. To generate the time series of future periods, daily data for the statistical period 1989-2019 were used and the trend of its changes was analyzed using Mann-Kendall test. The results showed that LARS-WG6 software simulates the minimum values of the minimum temperature well with low error indicators. Also, based on the results of the HadGM2-ES global model output in the study area, the minimum temperature in the future period will be higher than the base period in all scenarios and periods. The intensity of this increase under the RCP8.5 scenario is related to the last period of the century (2080-2061) and its lesser extent is related to the period (2060-2041) under the RCP4.5 scenario. Examination of seasonal averages also shows that spring has a lower temperature increase and autumn has a higher temperature increase. The trend of changes shows that the trend is positive and negative in both directions, so that in most stations and scenarios in different forecast periods, spring will have the most positive trend and autumn will have the most negative trend. Therefore, it can be concluded that the temperature will increase in future periods and the effect of cold waves will decrease.